Effect of high intensity focused ultrasound (HIFU) in conjunction with a nanomedicines-microbubble complex for enhanced drug delivery - Han, Hyounkoo; Lee, Hohyeon; Kim, Kwangmeyung; Kim, Hyuncheol (ELSEVIER SCIENCE BV, 2017)
Although nanomedicines have been intensively investigated for cancer therapy in the past, poor accumulation of nanomedicines in tumor sites remains a serious problem. Therefore, a novel drug delivery system is required to enhance accumulation and penetration of nanomedicines at the tumor site. Recently, high-intensity focused ultrasound (HIFU) has been highlighted as a non-invasive therapeutic modality, and showed enhanced therapeutic efficacy in combination with nanomedicines. Cavitation effect induced by the combination of HIFU and microbubbles results in transiently enhanced cell membrane permeability, facilitating improved drug delivery efficiency into tumor sites. Therefore, we introduce the acoustic cavitation and thermal/mechanical effects of HIFU in conjunction with microbubble to overcome the limitation of conventional drug delivery. The cavitation effect maximized by the strong acoustic energy of HIFU induced the preferential accumulation of nanomedicine locally released from the nanomedicines-microbubble complex in the tumor. In addition, the mechanical effect of HIFU allowed the accumulated nanomedicines to penetrate into deeper tumor region. The preferential accumulation and deeper penetration of nanomedicines by HIFU showed enhanced therapeutic efficacy, compared to low frequency ultrasound (US). These overall results demonstrate that the strategy combined nanomedicines-microbubble complex with HIFU is a promising tools for cancer therapy.
Keywords: PANCREATIC-CANCER; TARGETED DELIVERY; TUMOR-DIAGNOSIS; CONTRAST AGENTS; NANOPARTICLES; THERAPY; PACLITAXEL; CHEMOTHERAPY; GEMCITABINE; CAVITATION